O Brand Equity em instituições de ensino superior semipresenciais de natureza privada: um estudo na perspectiva do público consumidor - Rocha, Ronielle Medeiros (2023)
The rise in demand for higher education stimulates competitiveness among these large institutions, generating concern regarding the development of strategies that attract students and enhance the brand. From this perspective, the objective is to analyze the students' perception of the dimensions that make up the brand equity of private HEIs that opt for blended teaching with centers in the city of Piripiri - PI. For this, the theoretical model CCBE – brand value of HEIs was adopted, as a fundamental foundation for the development of the research, which is based on the dimensions University Experience; Controlled Communication; Word of Mouth Electronic/e-WOM; Co-Creation; Brand Awareness; Brand Associations and Total Brand Value, proposed by the theoretical model authored by Feitor (2016), with the specific objectives guided by the analysis of each of these dimensions in the referred institutions. The research has a quantitative approach, of the field research type, carried out through a survey with undergraduate students from the two institutions that opted for the blended teaching method in the city of Piripiri, in order to measure the determining factors in the value of their brands, in this In this sense, the data were analyzed using the descriptive statistical analysis technique. Through results expressed by means and medians, it was observed that, in general, that the two institutions have been able to manage their brands satisfactorily, considering that their direct consumers respond well to the initiatives of the HEIs regarding the relationship with the same. As for the benefits of the study, it is expected that the results can contribute to the understanding of the factors that students consider when entering HEIs, as well as resulting in an evaluation instrument that can be used by institutions as marketing strategies. In view of this, the investigation into the factors that make up the Brand Equity of HEIs can represent, for the managers themselves, a current panorama of how their brand is positioned before their students.